Explosion-prevention strategies of airflow controlling and closed-inerting for hydrogen dilution in utility tunnel. (30th April 2023) - Shao, Xiangyu; Shi, Wenyi; Li, Panpan; Pu, Liang; Zheng, Ligang; Lu, Chang; Wang, Jian; Gao, Jianliang
Abstract: Under the large-scale application of hydrogen energy and the acceleration of utility tunnel construction in China, the hydrogen pipeline would enter the utility tunnel soon. The explosion-prevention strategy is of important to hydrogen transportation in utility tunnel. Thus, a series of comparative studies were carried out in the present study, to explore the high efficiency dilution methods for unexpected hydrogen leak scenarios. (1) Effects of source type and domain extension were further validated based on our previous numerical model. The small-hole model was found to be simple and feasible for pipe release simulation, and has the same high accuracy like the notional nozzle model. The influence of unexpanded domain is acceptable. (2) Investigation of the explosion-prevention strategies was performed based on the finding of the worst leakage case, and hydrogen leaks at the middle of the upwind tunnel with upward leak direction was found to be the worst leakage case for the normal utility tunnel. (3) Compared with the layouts of lateral vents and the single horizontal air distributor, the middle exhaust vent was found to be the optimal airflow controlling strategy. (4) Furtherly, compared to the optimal airflow controlling strategy, closed-inerting was validated to be the most efficient dilution method. In the closed-inerting cases, the peak value of the flammable gas volume which is only ∼40% of the unimproved case appears. After that, the flammable cloud volume decays gradually, while the value increases steadily in the initial unimproved case. No obvious difference was found between the N2 and CO2 injection cases. Highlights: The hydrogen explosion-prevention strategies in utility tunnel were explored. The effects of source model and extension domain were clarified. The worst leakage case of leak location and leak direction was found. The airflow controlling and closed-inerting methods were studied.